2011
DOI: 10.1007/s10340-011-0383-0
|View full text |Cite
|
Sign up to set email alerts
|

Parasitoid complex of alfalfa aphids in an IPM intensive crop system in northern Catalonia

Abstract: Alfalfa aphids were monitored and aphid parasitism was determined in three crop-growing seasons (2007)(2008)(2009) in commercial alfalfa fields in valleys close to the Pyrenees, where an intensive arable crop rotation is practised under non-tillage and an integrated pest management system. Acyrthosiphon pisum, Therioaphis trifolii, and Aphis craccivora were the aphid species colonizing alfalfa fields but their occurrence varied between years. Thirteen Aphidiinae parasitoid species and four Aphelinidae from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 31 publications
0
19
0
1
Order By: Relevance
“…The parasitoid Aphidius ervi Haliday (Hymenoptera: Braconidae) and the predator Aphidoletes aphidimyza (Rondani) (Diptera: Cecidomyiidae) are among the most important natural enemies of this pest (Rabasse andvan Steenis 1999, Blümel 2004). These natural enemies have been recorded in spring in the production areas were orchards coexist with arable crops (Pons and Stary 2003, Miñarro et al 2005, Pons et al 2011 and both have been repeatedly found on M. persicae colonies in Prunus orchards early in spring (authors' unpublished data). However, M. persicae attacks Prunus sp.…”
Section: Introductionmentioning
confidence: 93%
“…The parasitoid Aphidius ervi Haliday (Hymenoptera: Braconidae) and the predator Aphidoletes aphidimyza (Rondani) (Diptera: Cecidomyiidae) are among the most important natural enemies of this pest (Rabasse andvan Steenis 1999, Blümel 2004). These natural enemies have been recorded in spring in the production areas were orchards coexist with arable crops (Pons and Stary 2003, Miñarro et al 2005, Pons et al 2011 and both have been repeatedly found on M. persicae colonies in Prunus orchards early in spring (authors' unpublished data). However, M. persicae attacks Prunus sp.…”
Section: Introductionmentioning
confidence: 93%
“…Conservation biological control involves the manipulation of the environment to enhance the effectiveness of natural enemies (Landis et al 2000) and is currently the only cost-effective biological control method in arable crops in many Mediterranean regions (Pons and Eizaguirre 2009;Pons et al 2011). The management of the environment may focus on the habitat, farm or landscape levels (Landis et al 2000), with scale-dependent effects on natural enemies (Tscharntke et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The incomplete turnover of the d 13 C signature to the new food source until nearly 4 weeks reveals the origin of an insect that has moved from one crop to another many days before. This interpretation is only possible if the adjacent crops do not share pests, as in the case of maize and alfalfa (Pons et al, 1994(Pons et al, , 2011 and other C3 crops, and may help to understand insect spillover between these kinds of crop.…”
Section: Discussionmentioning
confidence: 99%